PERFORMANCE MEASUREMENT USING THE BALANCED SCORECARD PERSPECTIVE OF CUSTOMER SERVICE AND INTERNAL BUSINESS PROCESSES ON THE PHARMACEUTICAL INSTALLATION PERFORMANCE OF KENDAL ISLAMIC HOSPITAL - Suwarni, Sri; Septiyana, Ria; Gloria, Fransisca; Uswati, Uswati (Lux Mensana: Journal of Scientific Health, 2024)
Introduction. Ensuring the quality of hospital services, quality control is carried out including monitoring and evaluation. One of the indicators is customer satisfaction and business processes aimed at measuring performance for the progress of the hospital. Method. This research used prospective observational research. Result & Analysis. Performance measurement of the Kendal Islamic Hospital Pharmacy Installation using the Balanced Scorecard method in terms of customer perspective with indicators of customer satisfaction and internal business process perspective with indicators of waiting time for concocted and non-concocted outpatient prescriptions, conformity of outpatient prescriptions with formularies, drug availability, and percentage of expired date and death stock drugs. Discussion. The results of the Balanced Score card approach in the Kendal Hospital Pharmacy Installation are “Fair” with an average score of 0.14. The customer perspective shows that patients are satisfied with the patient satisfaction index of 79.5%. Measurements from the perspective of internal business processes are quite good, the suitability of prescriptions with the formulary is 94.99%, the availability of drugs is 99.44% and death stock drugs are 1.08%, the waiting time for concocted drugs is 85.28% and non concocted 77.5%, expired drugs are 0.42%.